2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology 2009
DOI: 10.1109/wi-iat.2009.254
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Classification of Web Reports with Linguistic Text Mining

Abstract: In this paper we present a fuzzy system which provides a fuzzy classification of textual web reports. Our approach is based on usage of third party linguistic analyzers, our previous work on web information extraction and fuzzy inductive logic programming. Main contributions are formal models and prototype implementation of the system and evaluation experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The 90% overlap requirement may be hard to satisfy for small hot spot size or low R 1. For example, if a preset hot spot is [3437] and the EHE algorithm outputs [3436], the overlapping is 75%, which does not meet the 90% overlap constraint. When we relax the constraint to at least 50%, the accuracy jumps to over 90% in all cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 90% overlap requirement may be hard to satisfy for small hot spot size or low R 1. For example, if a preset hot spot is [3437] and the EHE algorithm outputs [3436], the overlapping is 75%, which does not meet the 90% overlap constraint. When we relax the constraint to at least 50%, the accuracy jumps to over 90% in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed algorithm showed that the clustering algorithm based on fuzzy set theory is easy to implement and has the capability to generate a highly flexible data structure for topic analysis and summarization with excellent performance. Dedek and Vojtas [37] presented a fuzzy system to provide classification of textual web reports. The major contribution of this work is to extract web information using fuzzy inductive logic.…”
Section: Related Workmentioning
confidence: 99%